Exploring the Therapeutic Potential of Phytohormones: Bridging Plant Immunity and Human Health - Neelesh Kumar Maurya; Neeti Kushwaha; Pratibha Arya; Aditi Rikhari; Gayatri Ramachandra (International Journal of Trends in Horticulture, 2024)
This review highlights the multifaceted roles of phytohormones, including salicylic acid, abscisic acid, cytokinins, and brassinosteroids, emphasizing their contributions to plant immunity and potential therapeutic applications in human health. Phytohormones are critical regulators of plant growth, development, and defense, functioning as signaling molecules that activate and coordinate plant responses to biotic and abiotic stresses. Salicylic acid, in particular, is instrumental in systemic acquired resistance (SAR), a defense mechanism that strengthens plant immunity by inducing the expression of pathogenesis-related proteins that deter pathogen attacks. This ability to enhance resistance helps plants maintain health and productivity, essential factors for food security and crop sustainability. In addition to their well-established functions in plant biology, recent studies suggest that phytohormones like salicylic acid, abscisic acid (ABA), cytokinins, and brassinosteroids may positively impact human health by influencing various metabolic pathways. Salicylic acid derivatives, including aspirin, are known for their anti-inflammatory and cardiovascular benefits, reducing blood clot formation and the risk of heart attacks. Abscisic acid has shown potential in modulating inflammation and improving insulin sensitivity through peroxisome proliferator-activated receptor gamma (PPARγ) activation, offering promising applications for managing metabolic syndrome and type 2 diabetes. Additionally, cytokinins and brassinosteroids exhibit strong antioxidant properties, helping neutralize free radicals and reduce oxidative stress, a factor implicated in aging and several chronic diseases, including cancer and neurodegenerative disorders. This unique intersection between plant biology and human health suggests that phytohormones could serve as valuable natural agents for preventing and managing diseases associated with inflammation, oxidative stress, and metabolic dysfunction. The continued exploration of phytohormones not only enhances our understanding of plant defense mechanisms but also opens new avenues for developing plant-derived therapeutic agents with the potential to improve human health and address chronic disease burdens globally.
Keywords: Anti-inflammatory; abscisic acid; antioxidant; cardiovascular health; glucose regulation; phytohormones; plant immunity; salicylic acid